Women, corporate governance and firm value. - See, Claudia Pei Jun. (2008)
This primary goal of this paper is to systematically assess the degree to which gender diversity will affect firm performance. We examine the announcement effects of female directors' appointment in Singapore-listed companies and explore several factors which may affect the firm value.